Intravenous thrombolysis for suspected ischemic stroke with seizure at onset. Issue 5 (9th September 2019) - Polymeris, Alexandros A.; Curtze, Sami; Erdur, Hebun; Hametner, Christian; Heldner, Mirjam R.; Groot, Adrien E.; Zini, Andrea; Béjot, Yannick; Dietrich, Annina; Martinez‐Majander, Nicolas; von Rennenberg, Regina; Gumbinger, Christoph; et al.
Abstract : Objective: Seizure at onset (SaO) has been considered a relative contraindication for intravenous thrombolysis (IVT) in patients with acute ischemic stroke, although this appraisal is not evidence based. Here, we investigated the prognostic significance of SaO in patients treated with IVT for suspected ischemic stroke. Methods: In this multicenter, IVT‐registry–based study we assessed the association between SaO and symptomatic intracranial hemorrhage (sICH, European Cooperative Acute Stroke Study II definition), 3‐month mortality, and 3‐month functional outcome on the modified Rankin Scale (mRS) using unadjusted and adjusted logistic regression, coarsened exact matching, and inverse probability weighted analyses. Results: Among 10, 074 IVT‐treated patients, 146 (1.5%) had SaO. SaO patients had significantly higher National Institutes of Health Stroke Scale score and glucose on admission, and more often female sex, prior stroke, and prior functional dependence than non‐SaO patients. In unadjusted analysis, they had generally less favorable outcomes. After controlling for confounders in adjusted, matched, and weighted analyses, all associations between SaO and any of the outcomes disappeared, including sICH (odds ratio [OR]unadjusted = 1.53 [95% confidence interval (CI) = 0.74–3.14], ORadjusted = 0.52 [95% CI = 0.13–2.16], ORmatched = 0.68 [95% CI = 0.15–3.03], ORweighted = 0.95 [95% CI = 0.39–2.32]), mortality (ORunadjusted = 1.49 [95% CI = 1.00–2.24], ORadjusted = 0.98 [95% CI = 0.5–1.92], ORmatched = 1.13 [95% CI = 0.55–2.33], ORweighted = 1.17 [95% CI = 0.73–1.88]), and functional outcome (mRS ≥ 3/ordinal mRS: ORunadjusted = 1.33 [95% CI = 0.96–1.84]/1.35 [95% CI = 1.01–1.81], ORadjusted = 0.78 [95% CI = 0.45–1.32]/0.78 [95% CI = 0.52–1.16], ORmatched = 0.75 [95% CI = 0.43–1.32]/0.45 [95% CI = 0.10–2.06], ORweighted = 0.87 [95% CI = 0.57–1.34]/1.00 [95% CI = 0.66–1.52]). These results were consistent regardless of whether patients had an eventual diagnosis of ischemic stroke (89/146) or stroke mimic (57/146 SaO patients). Interpretation: SaO was not an independent predictor of poor prognosis. Withholding IVT from patients with assumed ischemic stroke presenting with SaO seems unjustified. ANN NEUROL 2019;86:770–779